Self-healing and recyclable single-component caulking adhesive and preparation method thereof
By using a single group of components such as epoxy resin, polyurethane modified epoxy resin in the caulking glue to form multiple hydrogen bonds, the existing caulking glue has been solved by deteriorating the bonding performance and inability to heal itself in humid environments. The problem of self-healing and recycling of caulking glue is achieved, and the construction process is simplified.
Patent Information
- Application Number
- CN202411797495.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
AI Technical Summary
The bonding performance of existing caulking products in humid environments is degraded, and they are prone to bubbles or bulges. They have high cross-linking density, high hardness and brittle cracking, which cannot heal themselves. The two-component packaging is cumbersome and the construction is complicated.
Using a one-component caulking adhesive, which includes epoxy resin, polyurethane modified epoxy resin, blocked isocyanate, hydrazide, liquid rubber, thixotropic agent and pigment filler, formed by acylamine urea bond and urethane bond Multiple hydrogen bonds impart self-healing and recycling properties to the adhesive.
It achieves good bonding performance in humid environments, avoids bubbles and bulging phenomena, has the ability to self-heal and recycle with good flexibility and mechanical properties, simplifies the construction process and reduces material waste.
Smart Images

Figure CN119432301A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic polymer adhesives, and in particular to a self-healing and recyclable single-component caulking adhesive and a preparation method thereof. Background Art
[0002] In order to pursue beauty and improve the corrosion resistance of metal substrates, it is necessary to apply caulking adhesive on the gaps at the joints of steel plates of equipment and locomotives. According to the chemical properties of the materials, caulking adhesives are mainly divided into two categories: polyurethane and epoxy. The isocyanate (-NCO) in polyurethane caulking adhesives has high reactivity and is easy to react with water molecules in the environment to generate carbon dioxide, forming a large number of holes inside the colloid, causing the bonding and mechanical properties of the caulking adhesive to decrease, significantly shortening the service life. Therefore, when polyurethane caulking adhesives are used in a humid environment and on substrates that are not completely dehydrated, dense bubbles or local bulges will inevitably appear at the caulking site. Compared with polyurethane caulking adhesives, epoxy system caulking adhesives are not sensitive to moisture, and have the advantages of low cost, strong bonding, good corrosion resistance, and high mechanical properties, and are widely used in the industry. However, epoxy products have a high cross-linking density and high hardness. Under the destructive effects of factors such as alternating hot and cold environments, the colloid is prone to brittle cracking and loses its protective effect. Existing caulking glue products form a three-dimensional network structure after reaction. Once they are mechanically damaged or cracked, the cracks cannot heal or repair themselves, and the damaged caulking glue cannot be recycled and reused, resulting in material waste.
[0003] In addition, polyurethane and epoxy caulking glue are mostly two-component packaging, which requires accurate measurement and full mixing before construction. Not only does it increase the packaging cost, but the gluing process is also more cumbersome.
[0004] Therefore, in order to solve the problems existing in the prior art, it is necessary to provide a single-component packaged epoxy caulking adhesive which has good flexibility, self-healing properties and can be recycled. Summary of the invention
[0005] The purpose of the present invention is to provide a self-healing and recyclable one-component caulking adhesive and a preparation method thereof in view of the above-mentioned deficiencies in the prior art, by utilizing a large number of multiple hydrogen bonds that can be formed between acyl semicarbazide bonds and urethane bonds, thereby giving the one-component caulking adhesive good self-healing and recycling properties.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The first object of the present invention is to provide a self-healing and recyclable one-component caulking adhesive, the components of which include, by weight: 5.0 to 10.0 parts of epoxy resin, 7.0 to 20.0 parts of polyurethane-modified epoxy resin, 5.0 to 10.0 parts of blocked isocyanate, 3.0 to 5.0 parts of hydrazide, 5.0 to 15.0 parts of liquid rubber, 2.0 to 5.0 parts of thixotropic agent, and 30.0 to 50.0 parts of pigments and fillers;
[0008] The structural formula of the polyurethane modified epoxy resin is shown in formula (I): Among them, R1 is At least one of; R2 is At least one of; R3 is
[0009] At least one of; wherein a, b and c are integers, and 6≤a≤11, 11≤b≤14, 15≤c≤34.
[0010] Furthermore, the preparation method of the polyurethane modified epoxy resin comprises the following steps:
[0011] S1. Add polyester or polyether diol and diisocyanate in a molar ratio of 1:2 to 2.2, and add 0.01% to 0.05% of the mass of the above-mentioned materials participating in the reaction. React at 70°C to 85°C for 1.5 to 4 hours;
[0012] S2, according to the total molar number of hydroxyl groups n -OH With n -NCO Equal, calculate and add hydroxyl-containing epoxy compound to the above product; continue the reaction at 70℃~85℃ for 3h~8h; cool down to obtain polyurethane modified epoxy resin.
[0013] Furthermore, the catalyst is any one or more of dibutyltin dilaurate, stannous isooctanoate, dibutyltin didodecylsulfide or dibutyltin diacetate.
[0014] Furthermore, the epoxy resin is any one of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, 1,6-butanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane glycidyl ether or glycerol glycidyl ether, or a mixture of at least two thereof.
[0015] Furthermore, the diisocyanate compound is at least one of isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and toluene diisocyanate.
[0016] Furthermore, the hydrazide curing agent is any one of 1,6-adipic acid dihydrazide, 1,8-suberic acid dihydrazide or 1,10-sebacic acid dihydrazide or a mixture of at least two thereof.
[0017] Furthermore, the liquid rubber is any one of 1,4-polybutadiene, carboxyl-terminated liquid nitrile rubber, and liquid carboxyl nitrile rubber, or a mixture of at least two of them.
[0018] Furthermore, the thixotropic agent is any one of nano-silicon dioxide, organic bentonite, hydrogenated castor oil, and polyamide wax, or a mixture of at least two of them.
[0019] Furthermore, the pigment filler is any one of titanium dioxide, organic kaolin, diatomaceous earth, montmorillonite, calcium carbonate, and magnesium sulfate, or a mixture of at least two of them.
[0020] The second object of the present invention is to provide a method for preparing the above-mentioned self-healing and recyclable one-component caulking adhesive, wherein the following components are prepared in parts by weight:
[0021] Epoxy resin 5.0 to 10.0 parts, polyurethane modified epoxy resin 7.0 to 20.0 parts, blocked isocyanate 5.0 to 10.0 parts, hydrazide 3.0 to 5.0 parts, liquid rubber 5.0 to 15.0 parts, thixotropic agent 2.0 to 5.0 parts, pigments and fillers 30.0 to 50.0 parts;
[0022] The above components are mixed evenly at room temperature, vacuum degassed, and then rolled 3 to 4 times with a three-roll grinder to make the particle size of the mixture less than 40 μm, thereby obtaining the one-component caulking adhesive.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention provides a self-healing and recyclable single-component caulking adhesive, the components of which include, by weight: 5.0 to 10.0 parts of epoxy resin, 7.0 to 20.0 parts of polyurethane-modified epoxy resin, 5.0 to 10.0 parts of blocked isocyanate, 3.0 to 5.0 parts of hydrazide, 5.0 to 15.0 parts of liquid rubber, 2.0 to 5.0 parts of thixotropic agent, and 30.0 to 50.0 parts of pigments and fillers. Under room temperature conditions, hydrazide and epoxy groups are chemically inert, and blocked isocyanate (needs to be heated to 130°C for activation and deblocking) does not react with the amino group of hydrazide. Therefore, the chemical properties of the components of the caulking adhesive are stable, so that it can be packaged as a single component. The steps of weighing, mixing, and venting bubbles required for two-component caulking agents are omitted, and the construction is simple and easy to operate.
[0025] (2) Under the curing conditions of powder coating (~190℃), the blocked isocyanate undergoes a deblocking reaction to release a highly active isocyanate functional group (-NCO). -NCO undergoes an addition reaction with the active hydrogen atoms in the hydrazide to form an acyl semicarbazide bond. A large number of multiple hydrogen bonds can be formed between the acyl semicarbazide bond and the urethane bond, giving the single-component caulking adhesive good self-healing and recycling properties.
[0026] (3) The molecular structure and molecular weight of polyurethane-modified epoxy resin are adjustable, which gives the caulking adhesive good flexibility and mechanical properties, preventing the cracking of the adhesive strip caused by changes in ambient temperature.
[0027] (4) The single-component caulking adhesive provided by the present invention can be cured in a graded gradient manner, thereby avoiding the generation of a large number of pores due to the sudden polymerization of the adhesive strip. At 130°C, the blocked isocyanate is activated and deblocked, reacting with hydrazide or hydroxyl; at 160°C to 180°C, hydrazide and epoxy resin undergo a cross-linking reaction. The graded gradient curing of the caulking adhesive prolongs the reaction exothermic cycle, inhibits the sudden polymerization of the adhesive strip due to concentrated heat release during the curing process, eliminates the pores in the adhesive strip, and improves product quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is the infrared spectrum of the polyurethane modified bisphenol A epoxy resin obtained in Example 1;
[0029] Figure 2 The DSC curve of the caulking adhesive prepared with polyurethane-modified epoxy resin obtained in Example 1;
[0030] Figure 3 The tensile properties of the caulking adhesive prepared with the polyurethane-modified epoxy resin obtained in Example 1;
[0031] Figure 4 The infrared spectrum of the polyurethane-modified epoxy resin obtained in Example 2;
[0032] Figure 5 The DSC curve of the caulking adhesive prepared with polyurethane-modified epoxy resin obtained in Example 2;
[0033] Figure 6 The tensile properties of the caulking adhesive prepared with the polyurethane-modified epoxy resin obtained in Example 2;
[0034] Figure 7 The DSC curve of the caulking adhesive prepared with polyurethane-modified epoxy resin obtained in Example 3;
[0035] Figure 8 The tensile properties of the caulking adhesive prepared with polyurethane-modified epoxy resin are obtained in Example 3. DETAILED DESCRIPTION
[0036] In order to explain the technical solution and beneficial effects of the present invention more clearly, the present invention is described in detail below in conjunction with the accompanying drawings and embodiments. It should be clear that the reference drawings described are only some embodiments of the present invention and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0037] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0038] Example 1
[0039] Add 0.0182g (0.05%) of dibutyltin dilaurate to polytetrahydrofuran diol (25.08g, 0.025mol) and isophorone diisocyanate (11.13g, 0.050mol) and react at 70°C for 4.0h. Then, add bisphenol A epoxy resin E44 (epoxy value 0.42eq / 100g) (11.91g, 0.050mol) and continue to react at 70°C for 8.0h. Cool down and filter to obtain polyurethane modified epoxy resin.
[0040] The chemical structure of the polyurethane modified epoxy resin obtained in Example 1 was determined by infrared spectrometer. Figure 1 The product is at 3412cm -1 The absorption peak at 1717 cm is the absorption peak of -NH in the urethane bond. -1 The absorption peak at 1103cm is the absorption peak of C=O. -1 The absorption peak at 919 cm is the absorption peak of -O-. -1 The absorption peak at 2275cm -1 The absorption peak (-NCO) at 37° disappeared, indicating that the target product has been successfully synthesized.
[0041] 20.0 parts of polyurethane modified epoxy resin obtained in Example 1, 5.0 parts of bisphenol A epoxy resin (epoxy resin E-51), 10.0 parts of blocked isocyanate, 5.0 parts of 1,8-octanedioic acid dihydrazide, 15.0 parts of 1,4-polybutadiene (Evonik POLYVEST130), 5.0 parts of organic bentonite, and 50.0 parts of calcium carbonate. The above components are mixed evenly at room temperature, vacuum degassed and rolled three times with a three-roll mill, and the particle fineness of the mixture is less than 40 μm, so as to obtain a self-healing and recyclable single-component caulking adhesive.
[0042] 13.0 mg of the sealant obtained in Example 1 was added to a crucible and then placed in a DSC instrument to measure its thermal reaction performance. The test conditions were: heating from 20°C to 280°C at a heating rate of 20°C / min. The test results are as follows: Figure 2 As shown in the figure, the initial reaction temperature of the one-component caulking glue is 125.6℃, which is the deblocking temperature of the blocked isocyanate. Once the blocked isocyanate is deblocked, the released active isocyanate group quickly reacts with the hydrazide group or hydroxyl group to release heat. When the isocyanate in the system is completely consumed, the excess hydrazide group continues to react with the epoxy functional group until the hydrazide group or epoxy group is consumed (the test temperature is 240.3℃), and the reaction ends.
[0043] The prepared one-component caulking adhesive was squeezed into a polytetrafluoroethylene mold and cured in an oven at 180°C for 3 hours to produce flat thin plate samples with a thickness of 3 mm and 1 mm, respectively. The sample is soft and elastic, and the sample has no creases or cracks after being folded 50 times. The hardness of the sample with a thickness of 3 mm was measured by a rubber hardness tester (LX-A type). The hardness of the sample was measured to be 24.5-27.3, with an average value of 25.7.
[0044] Then, the sample with a thickness of about 1mm was cut into dumbbell-shaped specimens with a cutter. The tensile curve of the specimens was measured by a universal tensile machine. The crossbeam displacement speed was 50mm / min. The test results were as follows: Figure 3 As shown. Figure 3 It can also be seen that the tensile strength of the prepared sample is 5.27 MPa and the elongation is as high as 2210%, showing obvious tensile performance characteristics of low cross-linking rubber materials.
[0045] Cut the remaining material after cutting the standard sample strip and the material after breaking, lay it flat on two pieces of polyimide film, and then place it in a metal mold. Carefully place the metal mold in a flat vulcanizer, and measure the temperature of the flat vulcanizer to be 190℃~195℃, the pressure to be 10.0MPa~12.0MPa, and the insulation time to be 30min. Then take out the sample, cut it into dumbbell-shaped standard sample strips with a cutter, and measure the tensile curve of the sample strip with a universal tensile machine. The tensile speed is 50mm / min, and the above process is repeated 3 times. After 3 cycles, the tensile properties of the recycled sample strips were 4.23MPa, 4.08MPa and 3.85MPa, respectively. The tensile strength retention rate (E 回收 / E 原始 ) were 80.3%, 77.5% and 73.1% respectively. This shows that after the isocyanate group in the one-component epoxy caulking adhesive reacts with the hydrazide, a reversible bond and multiple hydrogen bonds between molecules are formed, giving the product better self-healing and recycling performance. Use a blade to randomly cut the cured adhesive strip into several sections and observe the cross section. The cross section is smooth and flat, and no pores of different sizes are formed. This shows that during the curing process of the one-component epoxy caulking adhesive, the reaction is relatively slow and no violent polymerization occurs.
[0046] The one-component epoxy caulking adhesive was sealed and stored at room temperature (20℃~35℃), and the viscosity of the adhesive was measured every one month. After 3 months of storage, the viscosity change of the sample was ≤15%. This shows that the one-component epoxy caulking adhesive has good room temperature storage stability.
[0047] Example 2
[0048] Polyethylene glycol (13.17 g, 0.020 mol), dicyclohexylmethane diisocyanate (11.54 g, 0.044 mol), 0.0026 g (0.01%) of stannous isooctanoate were added, and the mixture was reacted at 85°C for 1.5 h. Then, bisphenol F epoxy resin (0.45 eq / 100 g) (10.69 g, 0.048 mol) was added, and the reaction temperature was maintained at 85°C for 3.0 h. The mixture was cooled and filtered to obtain polyurethane-modified bisphenol F epoxy resin.
[0049] The chemical structure of the polyurethane modified epoxy resin obtained in Example 2 was determined by infrared spectrometer. Figure 4 The product is at 3406cm -1 The absorption peak at 1721 cm is the absorption peak of -NH in the urethane bond. -1 The absorption peak at 1107cm is the absorption peak of C=O. -1 The absorption peak at 917 cm is the absorption peak of -O-. -1 The absorption peak at 2275cm -1The nearby absorption peak (-NCO) disappears, indicating that the target product has been successfully synthesized.
[0050] 7.0 parts of the obtained polyurethane modified epoxy resin, 10.0 parts of bisphenol F epoxy resin, 5.0 parts of blocked isocyanate, 3.0 parts of 1,6-adipic acid dihydrazide, 5.0 parts of carboxyl-terminated liquid nitrile rubber (HYPRO 1300×8 produced by CVC), 2.0 parts of nano-silica thixotropic agent, 5.0 parts of titanium dioxide, 7 parts of montmorillonite, and 18 parts of calcium carbonate were mixed evenly at room temperature, vacuum degassed, and rolled three times with a three-roll mill. The particle fineness of the mixture was less than 40 μm, and a self-healing and recyclable single-component caulking adhesive was obtained.
[0051] 9.7 mg of the sealant obtained in Example 2 was added to the crucible, and then placed in a DSC instrument to measure its thermal reaction performance. The test conditions were: heating from 20°C to 280°C at a heating rate of 20°C / min. The test results are as follows: Figure 5 As shown in the figure, the initial reaction temperature of the one-component caulking glue is 126.1℃, which can be attributed to the deblocking temperature of the blocked isocyanate. Once the blocked isocyanate is deblocked, the released active isocyanate group will quickly react with the hydrazide group or hydroxyl group to release heat. When the isocyanate in the system is completely consumed, the excess hydrazide group continues to react with the epoxy functional group until the hydrazide group or epoxy group is consumed (the test temperature is 242.5℃), and the reaction ends.
[0052] The one-component epoxy caulking adhesive prepared in Example 2 was squeezed into a polytetrafluoroethylene mold and cured in an oven at 180°C for 3 hours to prepare flat thin plate samples with a thickness of 3 mm and 1 mm, respectively. The sample was soft and elastic, and the sample had no creases or cracks after being folded 50 times. The hardness of the sample with a thickness of 3 mm was measured by a rubber hardness tester (type LX-A). The hardness of the sample was measured to be 20.8-23.7, with an average value of 21.4.
[0053] Then, the sample with a thickness of about 1mm was cut into dumbbell-shaped specimens with a cutter. The tensile curve of the specimens was measured by a universal tensile machine. The crossbeam displacement speed was 50mm / min. The test results were as follows: Figure 3 As shown. Figure 6 It can also be seen that the tensile strength of the prepared sample is 4.34 MPa, and the elongation is as high as 2110%, showing obvious tensile performance characteristics of low cross-linking rubber materials.
[0054] Cut the remaining material after cutting the standard sample strip and the material after breaking, lay it flat on two pieces of polyimide film, and then place it in a metal mold. Carefully place the metal mold in a flat vulcanizer, and measure the temperature of the flat vulcanizer to be 190-195°C, the pressure to be 10.0MPa-12.0MPa, and the insulation time to be 30min. Then take out the sample, cut it into dumbbell-shaped standard sample strips with a cutter, and measure the tensile curve of the sample strip with a universal tensile machine. The tensile speed is 50mm / min, and the above process is repeated 3 times. After 3 cycles, the tensile properties of the recovered sample strips were 3.67MPa, 3.40MPa and 3.29MPa, respectively. The tensile strength retention rate (E 回收 / E 原始 ) were 84.6%, 78.1% and 75.7% respectively. This shows that the isocyanate group in the one-component epoxy caulking adhesive reacts with the hydrazide to form a reversible bond and multiple hydrogen bonds between molecules, giving the product better self-healing and recycling performance. Use a blade to randomly cut the cured adhesive strip into several sections and observe the cross section. The cross section is smooth and flat, and no pores of different sizes are formed. This shows that during the curing process of the one-component epoxy caulking adhesive, the reaction is relatively mild and no violent polymerization occurs.
[0055] The one-component caulking adhesive obtained in Example 2 was sealed and stored at room temperature (20°C to 35°C), and the viscosity of the adhesive was measured every one month. After 3 months of storage, the viscosity of the sample changed by ≤10%, indicating that the one-component epoxy caulking adhesive has good room temperature storage stability.
[0056] Example 3
[0057] Add 0.0125 g (0.03%) of stannous isooctanoate to polycaprolactone diol (30.01 g, 0.020 mol) and diphenylmethane diisocyanate (10.51 g, 0.042 mol) and react at 75°C for 2.5 h. Then, add hydrogenated bisphenol A epoxy resin (0.43 eq / 100 g) (10.25 g, 0.044 mol) and continue to react at 75°C for 7.0 h. Cool down and filter to obtain polyurethane-modified hydrogenated bisphenol A epoxy resin.
[0058] 13.0 parts of synthesized polyurethane modified hydrogenated bisphenol A epoxy resin, 5.0 parts of bisphenol F epoxy resin, 2.0 parts of phenolic epoxy resin, 6.5 parts of blocked isocyanate, 2.5 parts of 1,6-adipic acid dihydrazide, 1.5 parts of 1,10-sebacic acid dihydrazide, 8.5 parts of liquid carboxyl nitrile rubber (Tianyuan Aviation Materials), 1.0 parts of nano-silica thixotropic agent, 1.5 parts of hydrogenated castor oil, 15.0 parts of organic kaolin, 7 parts of diatomaceous earth, and 18 parts of calcium carbonate. The above components are mixed evenly at room temperature, vacuum degassed and rolled three times with a three-roll mill, and the particle fineness of the mixture is less than 40μm, so as to obtain a self-healing and recyclable single-component caulking adhesive.
[0059] 10.6 mg of the sealant obtained in Example 3 was added to the crucible, and then placed in a DSC instrument to measure its thermal reaction performance. The test conditions were: heating from 20°C to 280°C at a heating rate of 20°C / min. The test results are as follows: Figure 7 As shown in the figure, the initial reaction temperature of the one-component caulking glue is 128.3℃, which can be attributed to the deblocking temperature of the blocked isocyanate. Once the blocked isocyanate is deblocked, the released active isocyanate group will quickly react with the hydrazide group or hydroxyl group to release heat. When the isocyanate in the system is completely consumed, the excess hydrazide group continues to react with the epoxy functional group until the hydrazide group or epoxy group is consumed (the test temperature is 241.2℃), and the reaction ends.
[0060] The one-component epoxy caulking adhesive prepared in Example 3 was squeezed into a polytetrafluoroethylene mold and cured in an oven at 180°C for 3 hours to prepare flat thin plate samples with a thickness of 3 mm and 1 mm, respectively. The sample was soft and elastic, and the sample had no creases or cracks after repeated folding 50 times. The hardness of the sample with a thickness of 3 mm was measured by a rubber hardness tester (type LX-A). The hardness of the sample was measured to be 28.3-31.2, with an average value of 29.7.
[0061] Then, the sample with a thickness of about 1mm was cut into dumbbell-shaped specimens with a cutter. The tensile curve of the specimens was measured by a universal tensile machine. The crossbeam displacement speed was 50mm / min. The test results were as follows: Figure 8 As shown. Figure 8 It can also be seen that the tensile strength of the prepared sample is 7.45 MPa and the elongation is as high as 1350%.
[0062] Cut the remaining material after cutting the standard sample strip and the material after breaking, lay it flat on two pieces of polyimide film, and then place it in a metal mold. Carefully place the metal mold in a flat vulcanizer, and measure the temperature of the flat vulcanizer to be 190℃~195℃, the pressure to be 10.0MPa~12.0MPa, and the insulation time to be 30min. Then take out the sample, cut it into dumbbell-shaped standard sample strips with a cutter, and measure the tensile curve of the sample strip with a universal tensile machine. The tensile speed is 50mm / min, and the above process is repeated 3 times. After 3 cycles, the tensile properties of the recycled sample strips were 5.93MPa, 5.52MPa and 5.26MPa, respectively. The tensile strength retention rate (E 回收 / E 原始 ) were 79.6%, 74.1% and 70.6% respectively. This shows that after the isocyanate group in the one-component epoxy caulking adhesive reacts with the hydrazide, a reversible bond and multiple hydrogen bonds between molecules are formed, giving the product better self-healing and recycling performance. The cured adhesive strip was randomly cut into several sections with a blade and the cross section was observed. The cross section was smooth and flat, with no large or small pores formed, indicating that the obtained one-component epoxy caulking adhesive had a mild reaction and no violent polymerization occurred.
[0063] The one-component epoxy caulking adhesive obtained in Example 3 was sealed and stored at room temperature (20°C to 35°C), and the viscosity of the adhesive was measured every one month. After storage for 3 months, the viscosity change of the sample was ≤10%. This shows that the one-component epoxy caulking adhesive has good room temperature storage stability.
[0064] Example 4
[0065] Add 0.0192g (0.04%) of dibutyltin diacetate to polypropylene glycol (40.07g, 0.020mol) and toluene diisocyanate 80 / 20 (7.45g, 0.043mol) and react at 80°C for 2.0h. Then, add glycidol (3.42g, 0.046mol) and continue to react at 80°C for 6.0h. Cool down and filter to obtain polyurethane modified epoxy resin.
[0066] 10.0 parts of the above-synthesized polyurethane modified epoxy resin, 8.0 parts of polyurethane modified bisphenol A epoxy resin (Example 1), 3.0 parts of bisphenol A epoxy resin, 4.0 parts of phenolic epoxy resin, 9.0 parts of blocked isocyanate, 4.5 parts of 1,6-adipic acid dihydrazide, 0.5 parts of 1,8-octanedioic acid dihydrazide, 6.0 parts of liquid carboxyl nitrile rubber (Tianyuan Aviation Materials), 6.0 parts of 1,4-polybutadiene (Evonik POLYVEST 130), 3.0 parts of organic bentonite, 0.5 parts of polyamide wax, 12.0 parts of organic kaolin, 3.0 parts of magnesium carbonate, and 22.0 parts of calcium carbonate. The above components are mixed evenly at room temperature, vacuum degassed and rolled three times with a three-roll grinder, and the particle fineness of the mixture is less than 40 μm, so as to obtain a self-healing and recyclable single-component caulking adhesive.
[0067] Example 5
[0068] Add 0.0088g (0.025%) of dibutyltin (dodecylsulfide) to polytetrahydrofuran diol (10.04g, 0.010mol), polyethylene glycol (15.01g, 0.010mol), diphenylmethane diisocyanate (5.06g, 0.020mol), and hexamethylene diisocyanate (3.71g, 0.022mol), and react at 80°C for 3.5h. Then, add bisphenol A epoxy resin (0.42eq / 100g) (9.55g, 0.040mol) and hydrogenated bisphenol A epoxy resin (0.43eq / 100g) (0.95g, 0.004mol), and maintain the reaction temperature at 80°C for 6.0h. Cool down and filter to obtain polyurethane modified epoxy resin.
[0069] 7.0 parts of the above-synthesized polyurethane modified epoxy resin, 5.0 parts of bisphenol F epoxy resin, 3.0 parts of phenolic epoxy resin, 8.2 parts of blocked isocyanate, 4.0 parts of 1,6-adipic acid dihydrazide, 1.0 part of 1,8-octanedioic acid dihydrazide, 3.5 parts of terminal carboxyl liquid nitrile rubber (HYPRO 1300×8 produced by CVC), 3.5 parts of liquid carboxyl nitrile rubber (Tianyuan Aviation Materials), 2.8 parts of 1,4-polybutadiene (POLYVEST 130 produced by Evonik), 1.0 part of nano-silica, 1.0 part of organic bentonite, 0.5 part of polyamide wax, 12.0 parts of organic kaolin, 4.0 parts of montmorillonite, 3.0 parts of magnesium carbonate, and 24.0 parts of calcium carbonate. The above components are mixed evenly at room temperature, vacuum degassed and rolled three times with a three-roll grinder, and the particle fineness of the mixture is less than 40 μm, thereby obtaining a self-healing and recyclable single-component caulking adhesive.
[0070] Example 6
[0071] Add 0.0074g (0.02%) of stannous isooctanoate and 0.0075g (0.02%) of dibutyltin dilaurate to polytetrahydrofuran diol (15.13g, 0.015mol), polycaprolactone diol (10.00g, 0.005mol), dicyclohexylmethane diisocyanate (5.74g, 0.022mol), diphenylmethane diisocyanate (5.54g, 0.022mol), and react at 70°C for 4.0h. Then, add hydrogenated bisphenol A epoxy resin (0.43eq / 100g) (10.25g, 0.044mol), maintain the reaction temperature at 80°C and continue to react for 8.0h. Cool down and filter to obtain polyurethane-modified hydrogenated bisphenol A epoxy resin.
[0072] 15.0 parts of the above-synthesized polyurethane modified epoxy resin, 3.0 parts of bisphenol F epoxy resin, 3.0 parts of bisphenol A epoxy resin, 7.5 parts of blocked isocyanate, 3.0 parts of 1,10-decanedioic acid dihydrazide, 1.0 part of 1,8-octanedioic acid dihydrazide, 1.0 part of 1,6-adipic acid dihydrazide, 1.5 parts of terminal carboxyl liquid nitrile rubber (HYPRO 1300×8 produced by CVC), 13.5 parts of liquid carboxyl nitrile rubber (Tianyuan Aviation Materials), 1.0 part of nano silicon dioxide, 2.0 parts of organic bentonite, 2.0 parts of organic bentonite, 13.0 parts of organic kaolin, 2.5 parts of titanium dioxide, 3.0 parts of montmorillonite, and 22.5 parts of calcium carbonate. The above components are mixed evenly at room temperature, vacuum degassed and rolled three times with a three-roll grinder, and the particle fineness of the mixture is less than 40 μm, thereby obtaining a self-healing and recyclable single-component caulking adhesive.
[0073] Example 7
[0074] Add 0.0123 g (0.04%) of dibutyltin dilaurate to polycaprolactone diol (20.01 g, 0.020 mol) and diphenylmethane diisocyanate (10.51 g, 0.042 mol) and react at 70°C for 4.0 h. Then, add bisphenol F epoxy resin (0.45 eq / 100 g) (9.85 g, 0.044 mol) and continue to react at 80°C for 7.0 h. Cool down and filter to obtain polyurethane modified epoxy resin.
[0075] 17.0 parts of the above-synthesized polyurethane modified epoxy resin, 5.0 parts of bisphenol F epoxy resin, 2.0 parts of 1,4-butanediol diglycidyl ether, 8.5 parts of blocked isocyanate, 4.0 parts of 1,6-adipic acid dihydrazide, 1.0 part of 1,8-octanedioic acid dihydrazide, 3.5 parts of terminal carboxyl liquid nitrile rubber (HYPRO 1300×8 produced by CVC), 3.5 parts of liquid carboxyl nitrile rubber (Tianyuan Aviation Materials), 5.0 parts of 1,4-polybutadiene (POLYVEST 130 produced by Evonik), 1.0 part of nano-silica, 1.0 part of organic bentonite, 0.5 part of polyamide wax, 12.0 parts of organic kaolin, 4.0 parts of montmorillonite, 3.0 parts of magnesium carbonate, and 24.0 parts of calcium carbonate. The above components are mixed evenly at room temperature, vacuum degassed and rolled three times with a three-roll grinder, and the particle fineness of the mixture is less than 40 μm, thereby obtaining a self-healing and recyclable single-component caulking adhesive.
[0076] Example 8
[0077] Polyethylene glycol (6.57 g, 0.010 mol), polycaprolactone diol (20.01 g, 0.010 mol), diphenylmethane diisocyanate (10.51 g, 0.042 mol), 0.0075 g (0.02%) of stannous isooctanoate and 0.0079 g (0.02%) of di(dodecylsulfide) dibutyltin were added, and the mixture was reacted at 75°C for 3.5 h. Then, bisphenol A epoxy resin (0.42 eq / 100 g) (5.74 g, 0.024 mol) and glycidol (1.49 g, 0.020 mol) were added, and the reaction temperature was maintained at 75°C for 8.0 h. The mixture was cooled and filtered to obtain a polyurethane modified epoxy resin.
[0078] 17.0 parts of the above-synthesized polyurethane modified epoxy resin, 7.0 parts of bisphenol A epoxy resin, 1.0 part of glycerol glycidyl ether, 2.0 parts of phenolic epoxy resin, 10.0 parts of blocked isocyanate, 4.0 parts of 1,6-adipic acid dihydrazide, 1.0 part of 1,8-octanedioic acid dihydrazide, 3.5 parts of terminal carboxyl liquid nitrile rubber (HYPRO 1300×8 produced by CVC), 3.5 parts of liquid carboxyl nitrile rubber (Tianyuan Aviation Materials), 8.0 parts of 1,4-polybutadiene (POLYVEST 130 produced by Evonik), 1.0 part of nano-silica, 1.0 part of organic bentonite, 0.5 part of hydrogenated castor oil, 12.0 parts of organic kaolin, 4.0 parts of montmorillonite, 3.0 parts of magnesium carbonate, and 24.0 parts of calcium carbonate. The above components are mixed evenly at room temperature, vacuum degassed and rolled three times with a three-roll grinder, and the particle fineness of the mixture is less than 40 μm, thereby obtaining a self-healing and recyclable single-component caulking adhesive.
[0079] Example 9
[0080] Polyethylene glycol (16.01 g, 0.010 mol), polypropylene glycol (20.17 g, 0.010 mol), polycaprolactone diol (19.97 g, 0.010 mol), diphenylmethane diisocyanate (10.51 g, 0.042 mol), dicyclohexylmethane diisocyanate (5.74 g, 0.022 mol), 0.0169 g (0.03%) of stannous isooctanoate were added, and the mixture was reacted at 78°C for 4.0 h. Then, hydrogenated bisphenol A epoxy resin (0.43 eq / 100 g) (15.83 g, 0.068 mol) was added, and the reaction temperature was maintained at 75°C for 7.5 h. The mixture was cooled and filtered to obtain a polyurethane modified epoxy resin.
[0081] 6.5 parts of the above-synthesized polyurethane modified epoxy resin, 3.0 parts of bisphenol F epoxy resin, 3.0 parts of polypropylene glycol diglycidyl ether, 0.5 parts of trimethylolpropane glycidyl ether, 8.0 parts of blocked isocyanate, 3.0 parts of 1,6-adipic acid dihydrazide, 1.5 parts of 1,8-octanedioic acid dihydrazide, 3.5 parts of terminal carboxyl liquid nitrile rubber (HYPRO 1300×8 produced by CVC), 3.5 parts of liquid carboxyl nitrile rubber (Tianyuan Aviation Materials), 5.0 parts of 1,4-polybutadiene (POLYVEST 130 produced by Evonik), 1.5 parts of nano-silica, 1.0 parts of organic bentonite, 14.0 parts of organic kaolin, 3.0 parts of montmorillonite, 5.0 parts of magnesium carbonate, and 21.0 parts of calcium carbonate. The above components are mixed evenly at room temperature, vacuum degassed and rolled three times with a three-roll grinder, and the particle fineness of the mixture is less than 40 μm, thereby obtaining a self-healing and recyclable single-component caulking adhesive.
[0082] Example 10
[0083] Add 0.0091g (0.03%) of stannous isooctanoate and 0.0027 (0.01%) of dibutyltin dilaurate to polytetrahydrofuran diol (19.91g, 0.020mol), dicyclohexylmethane diisocyanate (5.51g, 0.021mol), hexamethylene diisocyanate (3.55g, 0.021mol), and react at 80°C for 3.0h. Then, add bisphenol A epoxy resin (0.42eq / 100g) (5.05g, 0.021mol), bisphenol F epoxy resin (0.45eq / 100g) (4.75g, 0.021mol) and glycidol (0.285g, 0.004mol), and maintain the reaction temperature at 80°C for 5.5h. Cool down and filter to obtain polyurethane modified epoxy resin.
[0084] 13.0 parts of the above-synthesized polyurethane modified epoxy resin, 4.0 parts of neopentyl glycol diglycidyl ether, 3.0 parts of 1,6-butanediol diglycidyl ether, 3.0 parts of phenolic epoxy resin, 5.0 parts of blocked isocyanate, 3.0 parts of 1,6-adipic acid dihydrazide, 1.5 parts of 1,8-octanedioic acid dihydrazide, 8.5 parts of liquid carboxyl nitrile rubber (Tianyuan Aviation Materials), 3.5 parts of 1,4-polybutadiene (Evonik POLYVEST 130), 1.0 part of nano-silica, 2.0 parts of organic bentonite, 0.5 parts of hydrogenated castor oil, 12.0 parts of organic kaolin, 4.0 parts of montmorillonite, 3.0 parts of diatomaceous earth, 3.0 parts of magnesium carbonate, and 24.0 parts of calcium carbonate. The above components are mixed evenly at room temperature, vacuum degassed and rolled three times with a three-roll grinder, and the particle fineness of the mixture is less than 40 μm, thereby obtaining a self-healing and recyclable single-component caulking adhesive.
[0085] Embodiment 11
[0086] Add 0.0139 g (0.04%) of dibutyltin dilaurate to polycaprolactone diol (14.91 g, 0.005 mol), polypropylene glycol (10.14 g, 0.005 mol), polytetrahydrofuran diol (10.04 g, 0.010 mol), diphenylmethane diisocyanate (5.29 g, 0.021 mol), toluene diisocyanate 80 / 20 (3.45 g, 0.020 mol), and react at 78°C for 3.0 h. Then, add hydrogenated bisphenol A epoxy resin (0.43 eq / 100 g) (9.75 g, 0.042 mol), maintain the reaction temperature at 83°C and continue to react for 6.0 h. Cool down and filter to obtain polyurethane-modified hydrogenated bisphenol A epoxy resin.
[0087] The above-synthesized polyurethane-modified hydrogenated bisphenol A epoxy resin 13.0 parts, bisphenol F epoxy resin 5.0 parts, polypropylene glycol diglycidyl ether 2.0 parts, trimethylolpropane glycidyl ether 1.0 parts, blocked isocyanate 8.2 parts, 1,6-adipic acid dihydrazide 4.0 parts, 1,8-octanedioic acid dihydrazide 1.0 parts, terminal carboxyl liquid nitrile rubber (CVC HYPRO 1300×8) 5.5 parts, 1,4-polybutadiene (Evonik POLYVEST 130) 5.0 parts, nano-silica 2.0 parts, organic bentonite 1.0 parts, diatomaceous earth 8.0 parts, organic kaolin 12.0 parts, montmorillonite 4.0 parts, magnesium carbonate 3.0 parts, calcium carbonate 24.0 parts. The above components are mixed evenly at room temperature, vacuum degassed and rolled three times with a three-roll grinder, and the particle fineness of the mixture is less than 40 μm, thereby obtaining a self-healing and recyclable single-component caulking adhesive.
[0088] Comparative Example 1
[0089] Add 0.0182 g (0.05%) of dibutyltin dilaurate to polytetrahydrofuran diol (25.08 g, 0.025 mol) and isophorone diisocyanate (11.13 g, 0.050 mol) and react at 70°C for 4.0 h. Then, add bisphenol A epoxy resin E44 (epoxy value 0.42 eq / 100 g) (11.91 g, 0.050 mol) and continue to react at 70°C for 8.0 h. Cool down and filter to obtain polyurethane modified epoxy resin. 20.0 parts of polyurethane modified epoxy resin, 5.0 parts of bisphenol A epoxy resin (epoxy resin E-51), 10.0 parts of diphenylmethane diisocyanate, 5.0 parts of 1,8-octanedioic acid dihydrazide, 15.0 parts of 1,4-polybutadiene (Evonik POLYVEST 130), 5.0 parts of organic bentonite, and 50.0 parts of calcium carbonate.
[0090] The above components were mixed at room temperature and ground with a three-roll mill. During the grinding process, the temperature and viscosity of the rubber increased. As the grinding time increased, the viscosity of the rubber increased significantly, the flow was difficult, the filler was not easily dispersed in the matrix resin, and normal construction could not be performed. This indicates that the unblocked isocyanate group reacted with dihydrazide at room temperature (it is impossible to package it as a single component), resulting in an increase in the viscosity of the rubber body, difficulty in dispersing the filler, and difficulty in construction. The prepared standard splines have the properties of self-healing and recyclability, but due to the uneven dispersion of the filler in the matrix resin, the performance of the splines is degraded and unstable.
[0091] Comparative Example 2
[0092] Add 0.0182 g (0.05%) of dibutyltin dilaurate to polytetrahydrofuran diol (25.08 g, 0.025 mol) and isophorone diisocyanate (11.13 g, 0.050 mol) and react at 70°C for 4.0 h. Then, add bisphenol A epoxy resin E44 (epoxy value 0.42 eq / 100 g) (11.91 g, 0.050 mol) and continue to react at 70°C for 8.0 h. Cool down and filter to obtain polyurethane modified epoxy resin. 20.0 parts of polyurethane modified epoxy resin, 5.0 parts of bisphenol A epoxy resin (epoxy resin E-51), 5.0 parts of 1,8-octanedioic acid dihydrazide, 15.0 parts of 1,4-polybutadiene (Evonik POLYVEST 130), 5.0 parts of organic bentonite, and 50.0 parts of calcium carbonate.
[0093] The above components are mixed at room temperature and ground with a three-roll grinder to a fineness of ≤40μm to obtain a single-component caulking adhesive. After curing according to the same curing process, the cured adhesive strip is randomly cut into several sections with a blade, and it is observed that there are dense pores on the cross section. The closer to the center of the adhesive strip, the larger and denser the pores. This phenomenon shows that the caulking adhesive undergoes violent polymerization during the curing process, and the reaction speed is faster and the heat concentration phenomenon is more serious near the center of the caulking adhesive strip. In addition, the sample strip prepared by the caulking adhesive obtained in Comparative Example 2 has the characteristics of non-recyclable and reusable, and can only be used once.
[0094] Comparative Example 3
[0095] 25.0 parts of bisphenol A epoxy resin (epoxy resin E-51), 5.0 parts of 1,8-octanedioic acid dihydrazide, 15.0 parts of 1,4-polybutadiene (Evonik POLYVEST 130), 5.0 parts of organic bentonite, and 50.0 parts of calcium carbonate. The above components are mixed at room temperature and ground with a three-roll grinder to a fineness of ≤40μm to obtain a single-component epoxy caulking adhesive. After curing according to the same curing process, the single-component epoxy caulking adhesive obtained in Comparative Example 3 has high hardness, no elasticity, is easy to crack when bent, and can only be used once.
[0096] The results of measuring the properties of the sealants prepared in Examples 1-11 and Comparative Examples 1-3 are shown in Table 1.
[0097] Table 1. Summary of the test results of the performance of the sealants obtained in the examples and comparative examples
[0098]
[0099] For matters not mentioned above, the prior art applies.
[0100] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make modifications or supplements to the described specific embodiments or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above implementations based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A self-healing and recyclable one-component caulking adhesive, characterized in that: The components thereof include, by weight: 5.0 to 10.0 parts of epoxy resin, 7.0 to 20.0 parts of polyurethane modified epoxy resin, 5.0 to 10.0 parts of blocked isocyanate, 3.0 to 5.0 parts of hydrazide, 5.0 to 15.0 parts of liquid rubber, 2.0 to 5.0 parts of thixotropic agent, and 30.0 to 50.0 parts of pigments and fillers; The structural formula of the polyurethane modified epoxy resin is shown in formula (I): Among them, R1 is At least one of; R2 is At least one of; R3 is At least one of; wherein a, b and c are integers, and 6≤a≤11, 11≤b≤14, 15≤c≤34.
2. The one-component caulking adhesive according to claim 1, characterized in that: The preparation method of the polyurethane modified epoxy resin comprises the following steps: S1. Add polyester or polyether diol and diisocyanate in a molar ratio of 1:2 to 2.2, and add 0.01% to 0.05% of the mass of the above-mentioned materials participating in the reaction. React at 70°C to 85°C for 1.5 to 4 hours; S2, according to the total molar number of hydroxyl groups n -OH With n -NCO Equal, calculate and add hydroxyl-containing epoxy compound to the above product; continue the reaction at 70℃~85℃ for 3h~8h; cool down to obtain polyurethane modified epoxy resin.
3. The one-component caulking adhesive according to claim 2, characterized in that: The catalyst is any one or more of dibutyltin dilaurate, stannous isooctanoate, dibutyltin didodecylsulfide or dibutyltin diacetate.
4. The one-component caulking adhesive according to claim 2, characterized in that: The epoxy resin is any one of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, 1,6-butanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane glycidyl ether or glycerol glycidyl ether, or a mixture of at least two thereof.
5. The one-component caulking adhesive according to claim 2, characterized in that: The diisocyanate compound is at least one of isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and toluene diisocyanate.
6. The one-component caulking adhesive according to claim 2, characterized in that: The hydrazide curing agent is any one of 1,6-adipic acid dihydrazide, 1,8-suberic acid dihydrazide or 1,10-sebacic acid dihydrazide or a mixture of at least two thereof.
7. The one-component caulking adhesive according to claim 2, characterized in that: The liquid rubber is any one of 1,4-polybutadiene, carboxyl-terminated liquid nitrile rubber, and liquid carboxyl nitrile rubber, or a mixture of at least two of them.
8. The one-component caulking adhesive according to claim 2, characterized in that: The thixotropic agent is any one of nano silicon dioxide, organic bentonite, hydrogenated castor oil and polyamide wax, or a mixture of at least two of them.
9. The one-component caulking adhesive according to claim 2, characterized in that: The pigment filler is any one of titanium dioxide, organic kaolin, diatomaceous earth, montmorillonite, calcium carbonate and magnesium sulfate, or a mixture of at least two of them.
10. A method for preparing a self-healing and recyclable one-component caulking adhesive according to any one of claims 1 to 9, characterized in that: Prepare the following components by weight: Epoxy resin 5.0 to 10.0 parts, polyurethane modified epoxy resin 7.0 to 20.0 parts, blocked isocyanate 5.0 to 10.0 parts, hydrazide 3.0 to 5.0 parts, liquid rubber 5.0 to 15.0 parts, thixotropic agent 2.0 to 5.0 parts, pigments and fillers 30.0 to 50.0 parts; The above components are mixed evenly at room temperature, vacuum degassed, and then rolled 3 to 4 times with a three-roll grinder to make the particle size of the mixture less than 40 μm, thereby obtaining the one-component caulking adhesive.